Cytokine levels in critically ill children with Severe Sepsis and their correlation with the severity of illness and mortality - Suresh Kumar Angurana; Arun Bansal; Jayashree Muralidharan; Ritu Aggarwal; Sunit Singhi (Wolters Kluwer Medknow Publications, 2018)
Objective: To study the baseline cytokine levels and their correlation with severity of illness and mortality in critically ill children with severe sepsis. Design: Subgroup analysis of a randomized, doubleblind, placebo-controlled trial. Setting: Pediatric intensive care unit of a tertiary care teaching hospital in North India. Patients: Fifty children, 3 months-12 years, with severe sepsis. Material and Methods: Blood was collected at admission for estimation of pro-inflammatory (IL-6, IL-12p70, IL-17, and TNF-α) and anti-inflammatory (IL-10 and TGF-β1) cytokines. Primary outcome: To find out correlation between cytokine levels with severity of illness (PRISM III score). Secondary outcomes: To compare cytokine levels among survivors and non-survivors. Results: Baseline pro-inflammatory cytokine levels [median (IQR)] were IL-6: 189 (35-285) pg/ml, IL-12p: 48 (28-98) pg/ml, IL-17: 240 (133-345) pg/ml, and TNF-α: 296 (198-430) pg/ml; anti-inflammatory cytokine levels were IL-10: 185 (62-395) pg/ml, and TGF-β1: 204 (92-290) ng/ml. The median (IQR) PRISM III score was 15 (12-20). Pro-inflammatory cytokines showed positive correlation with PRISM III score: IL-6 (Spearman's correlation coefficient, ρ=0.273, p=0.06), IL-12 (ρ=0.367, p=0.01), IL-17 (ρ=0.197, p=0.17), and TNF-α (ρ=0.284, p=0.05); and anti-inflammatory cytokines showed negative correlation: IL-10 (ρ= -0.257, p=0.09), and TGF-β (ρ= -0.238, p=0.11). The mortality was 10% (n=5). Among non-survivors, the levels of pro-inflammatory cytokines were significantly higher as compared to survivors [IL-6: 359 (251-499) vs. 157 (97-223) pg/ml, p=0.000; IL-12p70: 167 (133-196) vs. 66 (30-100), p=0.000; IL-17: 400 (333-563) vs. 237 (122-318), p=0.009; and TNF-α: 409 (355-503) vs. 330 (198-415), p=0.002, respectively]. Conclusion: In critically ill children with severe sepsis, pro-inflammatory cytokines showed a positive correlation with severity of illness and were significantly higher among non-survivors.